Adoption Of Green Building Technology (Gbt) In Managing Covid-19 Risk For Public Facilities Improvements - Nasaruddin, Norazura (Universiti Sains Malaysia, 2022)
In December 2019, the Novel Coronavirus Disease (COVID-19) outbreak began in Wuhan, China, spreading throughout China and globally. The building has become a critical connection in preventing and controlling COVID-19, an important location for people's work and living. Despite the struggles, being forced to remain indoors has increased our appreciation for how buildings can protect us from health risks such as COVID-19 while emphasizing the need for green buildings. To create a work-at-home environment that is both healthier and more comfortable for employees, eco-friendly construction methods are increasingly prevalent. According to an Ipsos survey, the GBT implementation promotes energy- and water-efficient practices, reducing households' utility bills, which have skyrocketed since vacating office facilities. Buildings also have an essential role in preventing and controlling the COVID-19 virus, according to the World Green Building Council (WGBC). Furthermore, during a global pandemic, green buildings can contribute to our health and help prevent the next. GBT, also known as Green Construction, is the application of environmentally responsible and resource-efficient design throughout the lifecycle of a structure, building, or commercial space. In addition to protecting precious natural resources, green buildings also enhance our quality of life. A healthy and comfortable living environment is necessary for mental and physical health. During the Covid-19 epidemic, Green Building Technology (GBT) adoption had multiple consequences on the tenants' sustainability. This research aimed to provide opinions and ideas regarding utilizing GBT to reduce the risk of COVID-19 infection and enhance public facilities for better pandemic resilience while combating the pandemic situations.